Omics approaches to investigate host–pathogen interactions in mass mortality outbreaks of Crassostrea gigas. (12th October 2018) - Nguyen, Thao V.; Alfaro, Andrea C.; Merien, Fabrice
Abstract: Mass mortality events are routinely reported in bivalve cultivation practices worldwide with significant economic consequences for the global aquaculture industry. Major contributors of these bivalve losses are infections caused by viruses and bacteria whose molecular action mechanisms are still not fully understood. This major bottleneck for shellfish cultivation presents an opportunity for fundamental research that can generate practical tools for reliable health assessments. To this end, newly developed omics approaches are likely to facilitate knowledge acquisition, especially if applied in conjunction with established and emergent immunological techniques. In recent years, various omics technologies (e.g. genomics, transcriptomics, proteomics and metabolomics) have been used to study the Pacific oyster mortality events associated with detection of ostreid herpesvirus type 1 (OsHV‐1) and Vibrio bacteria. These new approaches, especially when used in combination have significantly improved our understanding of this syndrome and associated diseases. In this paper, we review the current omics technologies that have been employed to investigate the interactions between Pacific oyster Crassostrea gigas and pathogens (e.g. OsHV‐1 and Vibrio sp.), infection mechanisms, host susceptibility and resistance. Herein, we also highlight some of the current challenges and future directions of omics approaches in shellfish health research, including disease detection, diagnosis and treatment.